PENERAPAN MODEL QUANTUM TEACHING PADA MATA PELAJARAN BAHASA ARAB DI MIS ISLAMIYAH MERABUAN - Meriyanti Meriyanti; Dewi Ferawati (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
The study aims to determine the process of appliying the quantum teaching model and evaluating student learning on Arabic language material at MIS Islamiyah Merabuan. The approach used in this research is a qualitative approach with a descriftive type of field research. In collecting data, researchers used interview, observasioan, and documentation thechniques. The data analysis thechniques used are data reduction, data display, and conclucions. To check the validity of data using triangulation and member check. The results of the research resulted in the application of the quantum teaching model to Arabic language material at MIS Islamiyah Merabuan using several steps including storttelling, forming groups, game, repetitation of material. Evaluation given by the teacher by giving an oral test.